Priming magnitude and retention in highly trained male volleyball players are unaffected by exercise type, muscle temperature, or viscoelasticity - Gepfert, M.; Terbalyan, A.; Helbin, J.; Thapa, R. K.; Stastny, P.; Krzysztofik, M.; Jarosz, J. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Background This study investigated delayed effects (6 h and 30 h) of a maximal isometric conditioning activity (ICA) versus a volleyball-specific warm-up (CON) on countermovement jump (CMJ) performance, viscoelastic properties (VP) of the rectus femoris (VP), and rectus femoris skin surface temperature (SST) in highly trained male volleyball players.